Seroprevalence of Q fever in sheep and goat in West Java area - Setiyono, Agus; Handharyani, Ekowati; Mahatmi, Hapsari (Indonesian Animal Sciences Society, 2008)
Q fever is a zoonotic disease caused by Coxiella burnetii, a species of bacteria that is distributed globally. Ruminant especially sheep and goats may play an important role in the transmission of the disease to human. The research of seroprevalence of Q fever in sheep and goats was carried out from August 2006 to March 2007 in West Java area. A total of 138 sera were collected; 69 sera from sheep and 69 sera from goats. The indirect immunoflourescent antibody test was used to determine the seroprevalence of Q fever. The seropositive based on the dilution of serum starting from 1 : 16. Seropositive were observed in 22 samples (31.88%) of sheep and 14 samples (20.28%) of goats. The highest titer of 1 : 128 was observed in 3 pregnant sheep. The results of the present study suggested that Q fever was endemic in West Java area. Key Words: Q Fever, Prevalence, Indirect Immunoflourescent Antibody Test